Is there a role for academia in drug discovery - Ivinson, Adrian J. (Henry Stewart Talks, 2013)
Increasing numbers of neurological disorders correlates with the growing numbers of elderly, Paucity of drugs that treat these neurological disorders, Reasons for this failure, Need to reassess the traditional division of labor between the for-profit sector and the not-for-profit academic sector, Transfer of the discovery phase to academia?, Other aspects of the heretofore-failed neuro drug discovery pipeline e.g. large-scale genetic studies aimed at unearthing new targets, The need to redefine the precompetitive space, The need to build new collaborations between companies, and between the commercial and academic sectors